2020
DOI: 10.1177/1076029620945039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Validity of SAMe-TT2R2 Score in a Cohort of Venous Thromboembolism Patients Treated With Warfarin

Abstract: Low SAMe-TT2R2 score of <2 was validated as a predictor of optimum anticoagulation control, reflected by mean time in therapeutic range (TTR) above 65% to 70%, among warfarin-treated atrial fibrillation patients. This study aimed to validate the ability of SAMe-TT2R2 score and its individual components in predicting anticoagulation control (mean TTR and clinical events) among a cohort of venous thromboembolism (VTE) patients in Qatar. A total of 295 patients were retrospectively evaluated. There was a trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…This could be attributed to the small sample size and relatively short follow‐up period. Furthermore, these findings are parallel to results of previous studies indicating low warfarin related complications in Qatar's population 28,29 . With regard to resource utilization after service transition, the current study revealed a significant decline in the frequency of INR testing and patients' compliance to attending scheduled clinic visits (a mean difference of 22.4).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This could be attributed to the small sample size and relatively short follow‐up period. Furthermore, these findings are parallel to results of previous studies indicating low warfarin related complications in Qatar's population 28,29 . With regard to resource utilization after service transition, the current study revealed a significant decline in the frequency of INR testing and patients' compliance to attending scheduled clinic visits (a mean difference of 22.4).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, these findings are parallel to results of previous studies indicating low warfarin related complications in Qatar's population. 28,29 30,31 Another aspect evaluated by this study was patients' satisfaction with drive-up testing and telehealth anticoagulation management. The provision of telehealth is generally limited by patients' access to hitech devices required to conduct a visit; internet access; level of comfort with technology and cultural acceptance of replacing in-person visits by virtual ones.…”
Section: Discussionmentioning
confidence: 99%